CATALYTIC ACTIVITY OF PAKISTANI CLAy MINERALS FOR FRIEDEL-CRAFTS ALKYLATION OF BENZENE AND NAPH THALENE: Short Communication - B, Ehsan; Ehsan, Abdul Mannan; Jamshed, Farhat; Khan, Izharul Haq (Biological Sciences - PJSIR, 2002)
Majority of the catalysts used by organic chemist are based on naturally occurring clays and minerals. These catalysts are prepared from the clays and minerals and are marketed by various chemical companies. The natural clays or minerals also find utility as a catalyst support and also suitable catalyst for the conversion of larger molecules. The clays supported reagents are known as pillared clays.